Ignorance of the Law is No Defence: Street Law as a Means to Reconcile this Maxim with the Rule of Law - Nciko, Arnold (Strathmore Law Review, 2018)
The age-long maxim, ignorance of the law is no defence, is a widely known presumption of law. This paper explains societal backdrops against which it has, from time to time, been contextualised. The aim is to prove that failure to present the law in a simplified and digestible form harms the rule of law. While the rule of law requires the capacity of the law to guide the layperson, the sheer number and complex nature of laws in modern States have made it virtually impossible for him or her to know the law. However, this paper does not seek to excuse ignorance of the law. Instead, it offers the street law programme as a panacea to reconcile this presumption with the rule of law. Further, with a particular reference to Kenya, it attempts to give a lesson for most African countries, where little or no attention has been paid to this programme.